2014
DOI: 10.5603/cj.a2013.0106
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical delay detected by tissue Doppler echocardiography is associated with the frequency of attacks in patients with lone atrial fibrillation

Abstract: Background: Our main purpose in this study is to compare atrial (inter-atrial, intra-left atrial, intra-right atrial) wave on electrocardiography to the A' wave on tissue Doppler trace was accepted as the atrial conduction time (PA'). The PA' time difference between the mitral annulus of left ventricle (ML) and the tricuspid annulus of right ventricle (TL) was defined as inter-atrial electromechanical delay (IA-EMD), the PA' time difference between the ML and septal mitral annulus (MS) as intra-left electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…These signs are positively correlated with EMD. Because of these histopathological changes taking place in AF pathophysiology, both lone AF and recurrence of AF after cardioversion has been shown to be closely related with EMD [ 41 , 42 , 43 ]. Similarly, we showed that prolongation of EMD predicted AF in hemodialysis patients in whom atrial hemodynamic, functional, and electrical parameters are directly affected.…”
Section: Discussionmentioning
confidence: 99%
“…These signs are positively correlated with EMD. Because of these histopathological changes taking place in AF pathophysiology, both lone AF and recurrence of AF after cardioversion has been shown to be closely related with EMD [ 41 , 42 , 43 ]. Similarly, we showed that prolongation of EMD predicted AF in hemodialysis patients in whom atrial hemodynamic, functional, and electrical parameters are directly affected.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between PA lateral and PA tricuspid (PA lateral-PA tricuspid) was defined as inter-atrial electromechanical delay (IA-EMD); the difference between PA septal and PA tricuspid (PA septal-PA tricuspid) was defined as intra-right electromechanical delay (IRight-EMD), and the difference between PA lateral and PA septal (PA lateral-PA septal) was defined as intra-left electromechanical delay (ILeft-EMD). 12,21 All measurements were performed by two experienced investigators who were unaware of each subject's clinical status. The reproducibility of electromechanical parameters was assessed by coefficients of variation (standard deviation of differences between the repeated measurements divided by the mean value and expressed in percent) between measurements.…”
Section: Assessment Of Left Atrial Mechanical Functionsmentioning
confidence: 99%
“…The echocardiographic measurement of atrial electromechanical delay has been shown to be correlated with the development of AF in several patient groups. 18) 19) Therefore, according to our study results, we can only hypothesize that LP patients with ongoing inflammation might have atrial electro-mechanical delay with a risk of AF development.…”
Section: Discussionmentioning
confidence: 78%